Khul’i As Mechanism To Preventing Murder Of Husband In Nigeria - Abubakar Ibrahim Adamu; Hamidu Ardo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Khul’i (right of redemption) is a right accorded to a wife to get a divorce from her husband from the bond of marriage either by initiating a divorce proceeding in a court or by a mutual consent of both parties and their representatives. Khul' is a form of divorce in which the wife releases herself (from the marriage tie) by paying consideration to the husband. If the husband does not consent to the divorce, a woman often goes to a mediating third party, such as an imam. Only a person versed in Islamic law i.e. a qadi, or Islamic Sharia court judge, can grant the khulʿ without the husband's consent. When petition for khulʿ is taken to the Sharia courts, a judge is permitted to substitute the husband and annul the marriage. This process of judicial annulment is also commonly referred to as faskh, which typically occurs when the husband refuses to consent to the wife's decision to divorce. This paper is aimed at providing a clear ad true picture of “Khul’” based on the Qur’an and Sunnah of the Prophet Muhammad (SAW) instead of murdering the husband. Analytical research methodology has been used in preparing this paper. Data are drawn from books, articles, scholarly journals etc.